HUBUNGAN KARAKTERISTIK AKSEPTOR KB BARU DENGAN PENGGUNAAN ALAT KONTRASEPSI MKET DAN NON MKET DI PUSKESMAS TEGALREJO YOGYAKARTA - Dewi Erlina Asrita Sari (STIKES HUSADA GEMILANG, 2018)
Indonesia population growth is high, at 1,4% a year. To reduce the population growth rate is by controlling the birth rate through birth control program. Contraceptive use vary according to education level, number of children, age, and occupation. The preliminary study in January-December displayed that there were 417 new acceptors with highest usage of contraception was IUD (324 acceptors; 60,3%), condom (12 acceptors; 2,87%), pills (10 acceptors; 2,39%), injection (51 acceptors; 12,2%), female sterilization (1 acceptors; 0,23%), while no one chose male sterilization. The purpose of this study is to identifytherelationship between characteristics of new birth control acceptors and the use of MKET and non-MKET contraception at Community Health Center of Tegalrejo Yogyakarta. This research was a cross-sectional descriptive analytic approach. The number of samples in this study were 57 respondents. Sample was taken by using total sampling. Data was analyzed by using Chi Square. The result showed there was no relationship between characteristics of new birth control acceptors and the use of MKET and non-MKET contraception at Community Health Center of Tegalrejo Yogyakarta (p > 0,05).